Performing the common good: volunteering and ethics in non-state crime prevention in South Africa. (21st July 2017) - Kirsch, Thomas G.
Abstract: Using fieldwork data from South Africa's Eastern Cape Province, this article highlights ambiguities of volunteering as idea and practice by exploring discursive strategies used by volunteers in the field of civic crime prevention when the ethical honesty and selflessness of their commitment to volunteering is questioned by others. These ambiguities relate to asymmetries in the relationship between donors and recipients of volunteering, as well as, most importantly, the challenge to determine what constitutes the 'common good'. This article demonstrates that these strategies entail the accommodation of contentions about: (1) the social identity of the volunteer by stressing the volunteer's commitment to abstract causes and objectives; (2) powerful asymmetries between donors and recipients of volunteering by invoking an encompassing sociality; and/or (3) the (alleged) self-interest of volunteers by defining the personal benefits achieved by volunteering not as an end in themselves but as 'private means' to 'public ends'. All three strategies have in common that volunteers as 'ethical subjects' can here be shown to be co-produced with South African 'communities of ethics' on different social scales. Résumé: S'appuyant sur des travaux menés dans la province de l'Eastern Cape en Afrique du Sud, cet article met en lumière les ambiguïtés du bénévolat en tant qu'idée et pratique en explorant des stratégies discursives utilisées par des bénévoles dans le domaine de la prévention civique de la criminalité lorsque certains mettent en doute l'honnêteté et l'altruisme éthiques de leur engagement. Ces ambiguïtés sont liées aux asymétries dans la relation entre donateurs et bénéficiaires du bénévolat, mais aussi et surtout à la difficulté de déterminer ce qui constitue le « bien commun ». L'article démontre que ces stratégies impliquent l'accommodement de points de divergence concernant : (1) l'identité sociale du bénévole en soulignant l'engagement du bénévole pour des causes et des objectifs abstraits ; (2) de fortes asymétries entre donateurs et bénéficiaires du bénévolat en invoquant une socialité englobante ; et/ou (3) l'intérêt personnel (présumé) des bénévoles en définissant les avantages personnels qu'offre le bénévolat non pas comme une fin en soi mais comme des « moyens privés » à des « fins publiques ». Ces trois stratégies ont en commun de montrer que les bénévoles, en tant que « sujets éthiques », sont coproduits avec des « communautés d'éthique » sud-africaines à diverses échelles sociales.